Early detection of brain damage in emergency department and the organ donation process: a case series - Aksoy, İskender and Pehlivanlar Küçük, Mehtap and Öztürk, Çağatay Erman and Baydın, Ahmet (The European Research Journal, 2018)
Brain death is defined as the irreversible loss of brain function following various pathophysiological changes. In many countries, the brain death diagnosis is carried out in conjunction with organ transplant programs. In Turkey, at third level health institutions in particular, healthcare units established entities that follow similar procedures. The increased number of patients waiting for organs and donor discovery studies have enhanced the public’s interest in this topic. Since the emergency department is usually the first line in admitting patients, its staff must have the firsthand knowledge of managing brain death and organ donation process. In this article, we present three clinical cases that we followed and diagnosed with brain death in our emergency department. Due to the lack of studies addressing brain death procedures in the emergency service, we believe that this report will greatly contribute to our awareness and handling of brain death treatment.